Development of a complete blood count with differential—based prediction model for in-hospital mortality among patients with acute myocardial infarction in the coronary care unit - Wang, Yu; Li, Changfu; Yuan, Miao; Ren, Bincheng; Liu, Chang; Zheng, Jiawei; Lin, Zehao; Ren, Fuxian; Gao, Dengfeng (Frontiers in Cardiovascular Medicine, 2022)
Purpose: In recent years, the complete blood count with differential (CBC w/diff) test has drawn strong interest because of its prognostic value in cardiovascular diseases. We aimed to develop a CBC w/diff-based prediction model for in-hospital mortality among patients with severe acute myocardial infarction (AMI) in the coronary care unit (CCU). Materials and Methods: This single-center retrospective study used data from a public database. The neural network method was applied. The performance of the model was assessed by discrimination and calibration. The discrimination performance of our model was compared to that of seven other classical machine learning models and five well-studied CBC w/diff clinical indicators. Finally, a permutation test was applied to evaluate the importance rank of the predictor variables. Results: A total of 2231 patient medical records were included. With a mean area under the curve (AUC) of 0.788 (95% confidence interval, 0.736–0.838), our model outperformed all other models and indices. Furthermore, it performed well in calibration. Finally, the top three predictors were white blood cell count (WBC), red blood cell distribution width-coefficient of variation (RDW-CV), and neutrophil percentage. Surprisingly, after dropping seven variables with poor prediction values, the AUC of our model increased to 0.812 (95% confidence interval, 0.762-0.859) (P＜0.05). Conclusions: We used a neural network method to develop a risk prediction model for in-hospital mortality among patients with AMI in the CCU based on the CBC w/diff test, which performed well and would aid in early clinical decision-making. The top three important predictors were WBC, RDW-CV and neutrophil percentage.